2014
DOI: 10.1007/s12031-014-0368-6
|View full text |Cite
|
Sign up to set email alerts
|

Different MicroRNA Profiles in Chronic Epilepsy Versus Acute Seizure Mouse Models

Abstract: Epilepsy affects around 50 million people worldwide, and in about 65 % of patients, the etiology of disease is unknown. MicroRNAs are small non-coding RNAs that have been suggested to play a role in the pathophysiology of epilepsy. Here, we compared microRNA expression patterns in the hippocampus using two chronic models of epilepsy characterised by recurrent spontaneous seizures (pilocarpine and self-sustained status epilepticus (SSSE)) and an acute 6-Hz seizure model. The vast majority of microRNAs deregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 75 publications
5
58
1
2
Order By: Relevance
“…We did not observe an increase in miR-134 after perforant pathway stimulation in the rat. This was surprising, although changes to miR-134 levels are not always detected after chemoconvulsive stimuli, 37 and we cannot rule out a technical explanation (e.g., the time points selected or a subfield-specific effect that was masked by the use of the whole hippocampus).…”
Section: Discussionmentioning
confidence: 82%
“…We did not observe an increase in miR-134 after perforant pathway stimulation in the rat. This was surprising, although changes to miR-134 levels are not always detected after chemoconvulsive stimuli, 37 and we cannot rule out a technical explanation (e.g., the time points selected or a subfield-specific effect that was masked by the use of the whole hippocampus).…”
Section: Discussionmentioning
confidence: 82%
“…3A ). A previous study identified miR-324-5p as one of several microRNAs that were downregulated in the hippocampus 24 hours following pilocarpine-induced status epilepticus (Kretschmann et al, 2015), but this result was not reproduced in a similar study using kainic acid to induce seizures (Jimenez-Mateos et al, 2011). Another study showed hippocampal upregulation of miR-324-5p in a rat epilepsy model 60 days following lithium-pilocarpine-induced status epilepticus (Song et al, 2011).…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies suggested that the miRNA profile is altered during epilepsy, 5,6 including the expression of miR-199a-5p. 7,8 miR-199a was also shown to be expressed specifically in neural tissues, such as the hippocampus, 9 and to be associated with neuronal process outgrowth, regeneration, and synaptic plasticity in damaged neurons through targeting mammalian target of rapamycin (mTOR). 10 In addition, miR-199a has been associated with apoptosis in many diseases.…”
mentioning
confidence: 99%